1987
DOI: 10.1111/j.1365-3083.1987.tb01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Alveolar Macrophages Synthesize Active Complement Components C6, C7, and C8 in Vitro

Abstract: We investigated whether serum-free human alveolar macrophage cultures synthesize active C6, C7, and C8. There was a significant binding of polyclonal anti-human C6 antibodies to agarose beads incubated with unstimulated macrophages for 24 or 48 h. Endotoxin stimulation of the macrophages was necessary for significant binding of polyclonal anti-C7 and anti-C8 antibodies to agarose beads co-cultured for 48 or 96 h. Two monoclonal antibodies (poly C9-MA and MCaE11) specific for a neoantigen of polymerized C9 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 7 publications
4
18
0
Order By: Relevance
“…Each sample was separated into plasma and hemocytes. The complement activation system in the plasma sample was modified in various ways by the following treatments [5, 11]: (1) adding EDTA to a final concentration of 10 m M (to inactivate both the classical and alternative pathways); (2) adding EGTA to a final concentration of 10 m M and Mg 2+ to a final concentration of 3.5 m M (to inactivate the classical pathway): (3) heat inactivation at 50°C for 20 min (to inactivate the alternative pathway), and (4) adding only phosphate-buffered saline (PBS; 200 µl) as control (no modification of the complement pathways). Hemocytes were washed twice with PBS and then resuspended in these plasma samples.…”
Section: Methodsmentioning
confidence: 99%
“…Each sample was separated into plasma and hemocytes. The complement activation system in the plasma sample was modified in various ways by the following treatments [5, 11]: (1) adding EDTA to a final concentration of 10 m M (to inactivate both the classical and alternative pathways); (2) adding EGTA to a final concentration of 10 m M and Mg 2+ to a final concentration of 3.5 m M (to inactivate the classical pathway): (3) heat inactivation at 50°C for 20 min (to inactivate the alternative pathway), and (4) adding only phosphate-buffered saline (PBS; 200 µl) as control (no modification of the complement pathways). Hemocytes were washed twice with PBS and then resuspended in these plasma samples.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, allotype conversion experiments, similar to those used in identifying the liver as the primary source of the complement proteins C3, C6, C8 and factor B, were not possible [5-71. Following the identification of the C7 M/N polymorphic system, similar experiments were performed on a group of liver transplant recipients which suggested that the liver contributed only 10 YO of the circulating C7 at time points later than 6 weeks post-transplantation [8]. In contrast, monocytes, macrophages, fibroblasts and astroglioma cell lines have directly or indirectly been shown to be capable of producing C7 [9-121.…”
Section: Introductionmentioning
confidence: 99%
“…These preparations were designat ed NHS-EGTAand NHS-EDTA. Another part of the serum pool was heated at + 50 °C for 20 min to inactivate the alternative pathway of complement activation (18). This preparation was designated NHS-50°.…”
Section: Preparation O F Seramentioning
confidence: 99%